Non-response bias in alcohol and drug population surveys - Zhao, J.; Stockwell, Tim; Macdonald, S. (Wiley-Blackwell Publishing Ltd., 2009)
Introduction and Aims: This proposed study was to assess non-response bias in the 2004 Canadian Addictions Survey (CAS). Design and Methods: Two approaches were used to assess non-response bias in the CAS which had a response rate of only 47%. First, the CAS sample characteristics were compared with the 2002 Canadian Community Health Survey (CCHS, response rate 77%) and the 2001 Canada Census data. Second, characteristics of early and late respondents were compared. Results: People with lowest income and less than high-school education and those who never married were under-represented in the CAS compared with the Census, but similar to the CCHS. Substance use was more prevalent in the CAS than the CCHS sample, but most of the CAS and CCHS estimates did not exceed tdthom±3% points. Late respondents were also significantly more likely to be male, young adult, highly educated, used, have high income, live in different provinces and report substance use. Multivariate logistic regression found significant non-response bias for lifetime, past 12 months, chronic risky, acute risky and heavy monthly alcohol use, lifetime and past year cannabis use, lifetime hallucinogen use, any illicit drug uses of lifetime and past year. Adjustment for non-response bias substantially increased prevalence estimates. For example, the estimates for lifetime and past 12 month illicit drug use increased by 5.22% and 10.34%. Discussion and Conclusions. It is concluded that non-response bias is a significant problem in substance use surveys with low response rates but that some adjustments can be made to compensate. © 2009 Australasian Professional Society on Alcohol and other Drugs.